DILEMA GURU AGAMA ISLAM ANTARA TUNTUTAN KURIKULUM DAN REALITA SOSIAL - Muharrir Alwathani (Yayasan An-Nur Meunara Baro, 2025)
Islamic Education (PAI) teachers face complex challenges in balancing the ideal demands of the national curriculum with the social realities experienced by students. This conflict manifests in the form of incongruities between normative teaching materials such as classical fiqh and the dynamic lives of modern youth, as well as curricular restrictions on discussing contemporary issues such as pluralism, gender, and tolerance in the classroom. This study employs a phenomenological qualitative approach through in-depth interviews and participatory observation with 20 PAI teachers across various educational levels in Indonesia. Curriculum documents were also analyzed to assess the extent of curricular openness to students’ social needs. The findings reveal that teachers experience a pedagogical dilemma between adhering to curricular mandates and responding ethically to students’ real-life contexts. Teachers navigate these tensions through creative transformation of official materials and embedding social values within classical religious discussions. The dilemma is further compounded by rigid educational bureaucracies and students’ resistance to content perceived as irrelevant. This study recommends contextual curriculum reforms and the strengthening of teacher training to bridge the gap between formal curriculum frameworks and lived student realities. Consequently, PAI teachers can remain relevant as moral agents amidst rapid social change.